Test-retest reliability of survey items on ownership and use of physical activity trackers - Ng, W. Kwok; Badura, Petr; Dzielska, Anna; Kokko, Sami; Woods, B. Catherine; Hamrik, Zdenek (Acta Gymnica, 2019)
Background: Researchers are interested in using digital tools, such as physical activity trackers (PAT), to promote and measure physical activity. PAT is a fast-growing research area that measures movement therefore, reliable questions on the ownership and use of PATs among adolescent populations need to be developed. Objective: The aim of this study was to conduct an intra-rater test-retest reliability study on PAT survey items used for surveillance purposes among young adolescents in ownership and use of smartphone applications (apps) and heart rate monitors (HRM). Methods: Young adolescents (N = 755; 11-, 13-, and 15-year-olds) in the Olomouc region of the Czech Republic were recruited to complete the questionnaire with a three-week gap during autumn 2017. Kappa statistics were used for measuring reliability. Results: When items were dichotomised into owners and non-owners, there was moderate agreement for boys (apps Kappa = .563, HRM Kappa = .575) and girls (apps Kappa = .447, HRM Kappa = .443). Conclusions: Measures in ownership and use of PAT can be assumed reliable among young adolescents.
Keywords: health promotion; wearable technology; activity trackers; school-age population; survey instrument; children